The Hyperthermophilic Restriction-Modification Systems of Thermococcus kodakarensis Protect Genome Integrity - Zatopek, Kelly M.; Burkhart, Brett W.; Morgan, Richard D.; Gehring, Alexandra M.; Scott, Kristin A.; Santangelo, Thomas J.; Gardner, Andrew F. (Frontiers in Microbiology, 2021)
Thermococcus kodakarensis (T. kodakarensis), a hyperthermophilic, genetically accessible model archaeon, encodes two putative restriction modification (R-M) defense systems, TkoI and TkoII. TkoI is encoded by TK1460 while TkoII is encoded by TK1158. Bioinformative analysis suggests both R-M enzymes are large, fused methyltransferase-endonuclease polypeptides that contain both restriction endonuclease (REase) activity to degrade foreign invading DNA and methyltransferase (MTase) activity to methylate host genomic DNA at specific recognition sites. In this work, we demonsrate T. kodakarensis strains deleted for either or both R-M enzymes grow more slowly but display significantly increased competency compared to strains with intact R-M systems, suggesting that both TkoI and TkoII assist in maintenance of genomic integrity in vivo and likely protect against viral- or plasmid-based DNA transfers. Pacific Biosciences single molecule real-time (SMRT) sequencing of T. kodakarensis strains containing both, one or neither R-M systems permitted assignment of the recognition sites for TkoI and TkoII and demonstrated that both R-M enzymes are TypeIIL; TkoI and TkoII methylate the N6 position of adenine on one strand of the recognition sequences GTGAAG and TTCAAG, respectively. Further in vitro biochemical characterization of the REase activities reveal TkoI and TkoII cleave the DNA backbone GTGAAG(N)20/(N)18 and TTCAAG(N)10/(N)8, respectively, away from the recognition sequences, while in vitro characterization of the MTase activities reveal transfer of tritiated S-adenosyl methionine by TkoI and TkoII to their respective recognition sites. Together these results demonstrate TkoI and TkoII restriction systems are important for protecting T. kodakarensis genome integrity from invading foreign DNA.